Effectiveness of falls prevention interventions for older adults newly discharged from hospital: a systematic review protocol - Naseri, Chiara; McPhail, S.; Francis-Coad, Jacqueline; Haines, T.; Etherton-Beer, C.; Morris, M.; Flicker, L.; Shorr, R.; Bulsara, M.; Netto, J.; Lee, D.; Waldron, N.; et al. (University of Adelaide * Faculty of Health Sciences, 2017)
Review objective: The objective of this review is to synthesize the best available evidence on the effectiveness of falls prevention interventions provided just prior or immediately after discharge from hospital on falls rates and falls injuries among older adults living in the community in the first 6 months after discharge from hospital.